Roles of Dopamine and Inflammation-Related Molecules in Behavioral Alterations Caused by Repeated Stress - Tomoyuki Furuyashiki (Elsevier, 2012)
Prolonged or intensive stress results in emotional and cognitive deficits and is a major risk factor for psychiatric disorders such as depression. Since the molecular mechanisms of how biological adaptations to stress go awry remains elusive, pharmaceutical development targeting stress has not been established. In rodents, repeated stress alters functions of multiple brain areas including the medial prefrontal cortex (mPFC) that confers stress resilience, thereby causing depression, anxiety, and working memory deficit. The mesocortical dopaminergic pathway that regulates such stress-coping functions is attenuated with repetition of stress via prostaglandin (PG) E2, a bioactive lipid derived from arachidonic acid, and its receptor EP1. Several findings suggest that microglia activated by repeated stress are involved in emotional and cognitive changes as a source of inflammation-related molecules such as PGE2 and IL-1β. IL-1 signaling is critical not only for emotional changes but also for microglial activation induced by repeated stress. Furthermore, purinergic signaling via the P2X7 receptor that can trigger PGE2 and IL-1β production in microglia has been implicated in the pro-depressive effect of repeated stress as well as depressive disorders. Collectively, inflammation-related molecules that link repeated stress to mPFC dysfunction are potential targets of pharmaceutical development for psychiatric disorders. Keywords:: stress, prefrontal cortex, dopamine, prostaglandin E2, microglia